2017
DOI: 10.1111/ajco.12764
|View full text |Cite
|
Sign up to set email alerts
|

Is definitive concurrent chemoradiotherapy effective for locally advanced head and neck cancer in the elderly aged ≥ 75 years: A single‐institute, retrospective, cohort study

Abstract: Definitive RT with or without systemic chemotherapy did not significantly influence DSS and OS for very elderly patients. Therefore, for elderly patients aged ≥ 75 years who have HNC, conservative RT might be sufficient for treatment purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…According to our search criteria, 2543 papers were initially identified. After sorting and removal of duplicates, 82 papers that fully fit our inclusion criteria were retrieved, reviewed in detail, and summarized in Tables according to the modality of treatment used: RT, systemic therapy (CT or targeted therapy), surgery, or multimodal therapy …”
Section: Introductionmentioning
confidence: 99%
“…According to our search criteria, 2543 papers were initially identified. After sorting and removal of duplicates, 82 papers that fully fit our inclusion criteria were retrieved, reviewed in detail, and summarized in Tables according to the modality of treatment used: RT, systemic therapy (CT or targeted therapy), surgery, or multimodal therapy …”
Section: Introductionmentioning
confidence: 99%
“…3-PS status :Our study observed a numerically better 3 years OS rate for patients who had a good PS (I) (60.7%) in comparison to PSII-III (42%), but this difference was not statistically significant (p=0.5). On the other hand, Lai et al 25 in their multivariate analysis for elderly HNC patients above 70 years found that PS above I was an independent factor for decreased OS HR was 2.312 (95%CI:1.176-4.546; P=0.015 1). Similarly, Sommers et al 26 confirmed that PS II and III associated with lower OS compared to PS0 HR was 3.14 (95% CI: 1.58-6.28 P=0.001).…”
Section: Factors Affecting Treatment Outcomementioning
confidence: 95%
“…[ 46 ] 2018 R 158 65 HNC CRT 70.6 29 3-year OS 50% G > 3 hematological toxicity (18) - Lai et al. [ 63 ] 2018 R 70 75 HNC CRT 60-74/30-37 - Median OS 10.8 vs 11.4 months (CRT vs RT group) G3/4 hematological toxicities: neutropenia (13.2), thrombocytopenia (5.3) - Wang et al. [ 64 ] 2019 R 1061 74 (70–88) Cervical cancer CRT 50.4/28 + 30-36/5-7 28.9 3-year OS 71.9% G3/4 hematological toxicity (58.1) G3/4 GI toxicity (8.6) Jingu et al.…”
Section: Planning and Treatment In Older Patientsmentioning
confidence: 99%